2016
DOI: 10.1021/acs.cgd.6b00791
|View full text |Cite
|
Sign up to set email alerts
|

Triple Helical Molecular Braid and Parallel Packed Wavy Chain-Based Supramolecular Organic Frameworks with Conformation- and Packing-Dependent Luminescent Properties

Abstract: Two three-dimensional supramolecular organic frameworks, [(H2bpdc)0.5(bipy)0.5] (1) and [(H3dpob)­(bipy)·3H2O] (2), have been successfully constructed and structurally characterized (H2bpdc = 2,2′-biphenyldicarboxylic acid; H3dpob = 3-(2′,3′-dicarboxylphenoxy)­benzonic acid; bipy = 4,4′-bipydine). 1 is driven by C–H···π hydrogen-bonded packing to three dimension. 2 origins form parallel-packed wavy chains and show π–π stacking-directed structure. After the SOFs are formed via weak noncovalent interaction, 1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The coordinated water molecules prevented the linkage between the neighboring chains into a higher dimensional structure. And luckily, the 1D chain was under helping of hydrogen bonding between PTA ligand and coordinated water molecule (O3‐H3c ⋅⋅⋅ O1=2.235 Å), giving a 2D “wave‐like” layer structure in ab plane (Figure c, d) . Thus 2D layers were arranged in a 3D supramolecular structure via the free water molecules (Figure e).…”
Section: Structural Description Of Pcp1mentioning
confidence: 95%
See 1 more Smart Citation
“…The coordinated water molecules prevented the linkage between the neighboring chains into a higher dimensional structure. And luckily, the 1D chain was under helping of hydrogen bonding between PTA ligand and coordinated water molecule (O3‐H3c ⋅⋅⋅ O1=2.235 Å), giving a 2D “wave‐like” layer structure in ab plane (Figure c, d) . Thus 2D layers were arranged in a 3D supramolecular structure via the free water molecules (Figure e).…”
Section: Structural Description Of Pcp1mentioning
confidence: 95%
“…And luckily,t he 1D chain was under helping of hydrogen bonding between PTAl igand and coordinated water molecule (O3-H3c···O1 = 2.235 ), giving a2 D" wave-like" layer structure in ab plane (Figure 1c,d). [23] Thus 2D layers were arrangedi na3D supramolecular structure via the free water molecules (Figure 1e). The PXRD patterns confirmed the crystalline purity of as-synthesized pcp1 ( Figure S1).…”
Section: Structural Description Of Pcp1mentioning
confidence: 99%
“…After the solvents were completely removed, HOF-1 could still readsorb gases and then show various emission intensities. Although a couple of the thermally stable HOFs were isolated and investigated recently, , , only a few related studies on the light emission properties of HOFs have been reported. We showed different contents of solvents in HOF-1 affect its framework packing, consequently producing various emission intensities. Surprisingly, the framework of HOF-1 was observed to almost recover after adsorbing solvents by the study of powder-XRD.…”
Section: Introductionmentioning
confidence: 85%
“…Through careful synthesis control, metal or ligand directed self-assembly can be consciously designed into a synthetic framework with interesting properties and useful applications in various fields like molecular recognition, chiroptical switching devices and gas storage materials. [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%